Strand Inventory Analysis of Post Tension in PT XYZ Using Discrete-Event Simulation Method - Fakhrana Oktia Dyahnawangsari; Ratih Dyah Kusumastuti (Quantitative Economics and Management Studies, 2024)
The development of connectivity infrastructure, particularly toll roads, is planned to continue expanding and reach 3,500 km by 2030. This signifies a positive outlook for the construction industry. This research conducted to analyse the management of post tension raw materials and determine the optimal policies using the discrete-event simulation method. Simulation scenarios were developed using the Arena application, taking into consideration the demand patterns for post tension work. The validation test results confirmed the capability of the base case model in accurately representing real-world conditions. Scenario development was carried out to influence the strand inventory pattern by incorporating reorder points and adjusting order sizes. Based on the scenario analysis, the most effective approach was found to be setting a reorder point of 3 tons and an order size of 5 tons. The implementation of this analysis successfully reduced the strand inventory by 58.78%. This research enables companies to optimize their inventory, reduce costs, and enhance operational efficiency. The findings contribute to the development of strategies that support sustainable growth in connectivity infrastructure in Indonesia.